2021
DOI: 10.3390/ijerph18084369
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Workforce Burnout in the COVID-19 Response in the U.S.

Abstract: While the health impacts of the COVID-19 pandemic on frontline health care workers have been well described, the effects of the COVID-19 response on the U.S. public health workforce, which has been impacted by the prolonged public health response to the pandemic, has not been adequately characterized. A cross-sectional survey of public health professionals was conducted to assess mental and physical health, risk and protective factors for burnout, and short- and long-term career decisions during the pandemic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 28 publications
(39 reference statements)
4
92
0
Order By: Relevance
“…This is comparable to the findings published by Roslan, Yusoff 19 and Apaydin, Rose, 38 who reported that 50% of Malaysian HCW and 43% of American HCW working in similar settings experienced burnout respectively. In contrast, Lu, Zhang, 18 Baptista, Teixeira, 39 and Stone, Kintziger 40 reported a higher prevalence of burnout among Chinese public health providers (58%), Portuguese primary care physicians (69%), and American public health workforce (66%) respectively. While the variation in prevalence may partly reflect the differences in COVID-19 burden in different regions and pandemic wave, a systematic review on burnout among physicians have indicated that the variability in prevalence estimates of burnout may also be attributed to variation in burnout definitions and assessment methods.…”
Section: Discussionmentioning
confidence: 92%
“…This is comparable to the findings published by Roslan, Yusoff 19 and Apaydin, Rose, 38 who reported that 50% of Malaysian HCW and 43% of American HCW working in similar settings experienced burnout respectively. In contrast, Lu, Zhang, 18 Baptista, Teixeira, 39 and Stone, Kintziger 40 reported a higher prevalence of burnout among Chinese public health providers (58%), Portuguese primary care physicians (69%), and American public health workforce (66%) respectively. While the variation in prevalence may partly reflect the differences in COVID-19 burden in different regions and pandemic wave, a systematic review on burnout among physicians have indicated that the variability in prevalence estimates of burnout may also be attributed to variation in burnout definitions and assessment methods.…”
Section: Discussionmentioning
confidence: 92%
“…It, therefore, becomes part of the mission of health politics to see that health-care organizations take responsibility for burnout prevention. All affected agencies must work to understand and address burnout syndrome both preventively and remedially [16]. It would be especially important to have a consensus between the Center for Disease Control and Prevention (CDC) and the WHO as the main health authorities.…”
Section: Key Pointsmentioning
confidence: 99%
“…We conducted a cross-sectional survey of individuals working in public health during the ongoing COVID-19 pandemic response. The survey assessed the public health workforce across a variety of domains such as professional experience (i.e., training, years of experience, content expertise, job functions), mental and physical health status (i.e., generalized anxiety, depression, burnout), and career plans (i.e., pre-pandemic vs. current career plans) [ 17 ] (See Supporting Information ). We pilot tested the survey for clarity and content with a group of epidemiologists working in a large, local public health department and revised the survey based on this feedback.…”
Section: Methodsmentioning
confidence: 99%